2016
DOI: 10.1002/joc.4818
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the Madden‐Julian oscillation on intraseasonal precipitation over Northeast Brazil

Abstract: The impacts of the Madden‐Julian oscillation (MJO) on precipitation over Northeast Brazil (NEB, also known as Nordeste) are evaluated based on daily raingauge data from 492 stations over 30‐year period (1981–2010). Composites of precipitation, outgoing longwave radiation and moisture‐flux anomalies are performed for each phase of the MJO, and over all four seasons, based on the Jones–Carvalho MJO index. To distinguish the MJO signal from other patterns of climate variability, daily data are filtered using a 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 91 publications
(232 reference statements)
1
14
0
3
Order By: Relevance
“…5, 6, 7). These results are consistent with those of (Valadão et al 2017;Alvarez et al 2016), who use station data and gridded station data, respectively, to demonstrate the seasonality of MJO teleconnections to precipitation in South America.…”
Section: South Americasupporting
confidence: 89%
“…5, 6, 7). These results are consistent with those of (Valadão et al 2017;Alvarez et al 2016), who use station data and gridded station data, respectively, to demonstrate the seasonality of MJO teleconnections to precipitation in South America.…”
Section: South Americasupporting
confidence: 89%
“…According to the literature, it is known that rainfall distribution in the NEB is not typical of equatorial areas in terms of volume, because different physical mechanisms are responsible for a remarkable interannual (Marengo and Bernasconi, ; Vieira et al ., ) and occasional intraseasonal variability (Valadão et al ., ), which result in three climate types: tropical, subtropical humid, and semiarid (Cavalcanti et al ., ). Figure shows the mean monthly accumulated rainfall in each capital city of the NEB in the period from 1988 to 2017 and allows the identification of some of these climate characteristics as well as the association with the occurrence of meteorological phenomena.…”
Section: Resultsmentioning
confidence: 99%
“…(Waliser, Murtugudde, Strutton, & Li, 2005) have found that Chlorophyll-a can vary at Madden-Julian Oscillation (MJO) time scales. MJO is an eastward moving strong contributor to various extreme events of rainfall, winds, clouds, and pressure that traverses in the tropics (Drushka et al, 2012;Valadão, Carvalho, Lucio, & Chaves, 2017). The is found to be influenced by the atmospheric variability, with periods of 30-60 days and eastward propagation of atmospheric convection cells (Hendon & Salby, 1994).…”
Section: Boosted Regression Treesmentioning
confidence: 99%